STRATEGI PENGUATAN EKONOMI DAN PEMBERDAYAAN PELAKU UMKM PASCA PANDEMI COVID 19 MELALUI G-25 - Mohtazul Farid; M. Ishak Abdus Salam (DIMENSI - Jurnal Sosiologi, 2023)
The impact of the COVID-19 pandemic on the economy is being felt. Globally, in 2020 trading volume decreased by around 32 percent. The social restriction policy has weakened businesses in the fields of transportation, tourism, trade and health. Household businesses have been the worst hit by Covid 19. Many Micro, Small and Medium Enterprises (MSMEs) have gone out of business. People's purchasing power is helpless. This article reveals several alternatives for strengthening the economy and empowering MSME actors, which are carried out by the G-25 community in Bangkalan Madura. This qualitative research data was obtained from the administrators, volunteers and beneficiaries of the G-25, through in-depth observations and interviews. There were 10 informants in this study.G-25 is a social community that is engaged in the social and economic fields of society. Its main activity is to collect funds from donors voluntarily. The funds were then used for community economic recovery activities after the pandemic. There are three main programs in strengthening the economy and empowering UMKM actors. Namely, the Social Charity assistance program, sustainable super micro UMKM empowerment and education empowerment programs for the poor. This research can be useful as a reference in designing models of economic strengthening, empowerment and business development of MSME actors after the COVID-19 pandemic..